High-temperature coupling inorganic composite adhesive material as well as preparation method and application thereof

By developing high -temperature coupling inorganic composite gum materials, combined with high -entropy metals, ceramics and boric acid, the problem of failure of ultrasonic coupling agent under high temperature conditions, real -time monitoring of high temperature in oil collection bolt stress, improved the reliability and monitoring reliability and improvement Safety.

CN119350980APending Publication Date: 2025-01-24CNOOC SAFETY & TECH SERVICES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680649.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Under high temperature conditions, existing ultrasonic coupling agents are difficult to work effectively and cannot meet the needs of oil production bolt stress monitoring.

Method used

The development of a high -temperature coupling inorganic composite glue material, using high -entropy metal AGCUNICR, ceramic material B4C and borate as the main component, prepare the material through mechanical stirring, and bond with ultrasonic probes to form a high -temperature ultrasound monitoring probe.

Benefits of technology

This material can effectively couple ultrasonic at 100-500 ° C, realize real-time monitoring of oil collection bolt stress, and improve the reliability and safety of monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350980A_ABST
    Figure CN119350980A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature coupling inorganic composite adhesive material as well as a preparation method and application thereof. The high-temperature coupling inorganic composite adhesive material comprises an inorganic adhesive matrix, a high-entropy metal toughening material and a ceramic wear-resistant and impact-resistant material, the inorganic adhesive matrix is borate, the high-entropy metal toughening material is AgCuNiCr, and the ceramic wear-resistant and impact-resistant material is B4C. According to the prepared AgCuNiCr-MBO3-B4C metal ceramic composite inorganic adhesive material, high toughness of metal and the strengthening effect of a ceramic material are combined, an inorganic adhesive coupling layer with high bonding strength is formed on the surface of the high-temperature oil extraction bolt, and the application requirement for stress measurement of the oil extraction bolt under the high-temperature condition is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high temperature bonding inorganic adhesive, and in particular to an AgCuNiCr-MBO for oil production bolts. 3 -B 4 C metal ceramic composite inorganic adhesive material and its preparation method and application. Background Art

[0002] Heavy oil reservoirs are characterized by deep burial depth, high pressure, and high viscosity. They are called "immobile oil". Currently, 70% of the world's remaining oil resources are heavy oil. The main method of heavy oil extraction is thermal extraction, which uses coal (oil) boilers to make pure water into high-temperature and high-pressure steam and inject it underground to heat the formation and crude oil, reduce the viscosity of crude oil, and extract the crude oil to the surface.

[0003] Heavy oil thermal recovery devices are exposed to harsh working conditions such as high temperature, corrosion, and sand in crude oil for a long time. They are susceptible to erosion and thermal stress, resulting in erosion thinning, reduced material strength, material creep, and even fracture, which in turn causes serious accidents such as steam leakage, crude oil leakage, and equipment failure. Most of the heavy oil thermal recovery wellhead devices are castings, and fastening connections (high-strength bolts) are an important assembly method. They are also important connection forms for double-tube six-way, ball valves, large and small four-way, and other parts. A set of thermal recovery systems uses more than 100 high-strength bolts. High-strength bolts mainly play the role of connection, force and torque transmission. During use, they are affected by long-term alternating loads and high-temperature corrosive environments, and are prone to creep and stress relaxation problems, leading to unplanned shutdowns. Therefore, the working safety and reliability of high-strength bolts will directly affect the safe, reliable and economical operation of the thermal recovery wellhead device. It is very necessary to study the stress monitoring and fatigue warning technology of high-strength bolts.

[0004] The measurement of bolt stress is an important detection link in engineering, which aims to ensure the reliability and safety of bolts. When performing bolt stress detection, a variety of methods can be used, including blind hole method, X-ray diffraction method, ultrasonic stress detection method, etc. These methods have their own advantages and disadvantages and are suitable for different detection needs and scenarios. Although the blind hole method can provide relatively accurate detection results, it requires damage to the structure of the material, so it is subject to certain restrictions in application. The X-ray diffraction method has been tested in the market, and the technology is mature and stable, but the disadvantage is that the detection instrument is bulky, the operation is time-consuming, and it is accompanied by radiation, which poses certain health risks to operators. The ultrasonic stress detection method is simple and fast to operate, and it does not damage the material or the detection personnel. Although it is a newer technology and the market inspection degree is not high enough, it is considered to be the most suitable method due to its non-destructive testing characteristics. Ultrasonic waves can sensitively reflect the information inside the test object, and ultrasound can be used to non-destructively measure the accumulated stress of the test object.

[0005] In addition, in industrial sites, torque wrenches are often used to simply determine the magnitude of the axial stress value of the bolt. However, due to the reverse torque effect between the nut part and the thread friction pair part and the elastic deformation of the bolt thread pair part, the torque that can actually cause the bolt to produce axial stress is less than 20% of the value on the torque wrench panel. In addition, the ultrasonic longitudinal wave non-destructive testing technology of the axial stress of the bolt using pulse echo reflection method, transit time method, phase method and other technologies can also effectively obtain the magnitude of the axial stress value of the bolt. According to the acoustic elasticity theory, there is a certain correspondence between the propagation speed of ultrasonic waves in isotropically homogeneous metal materials and the magnitude of the stress value, which provides a theoretical basis for the measurement of the axial stress of the bolt.

[0006] When using ultrasound to measure bolt stress, a coupling agent can be used at room temperature. However, when measuring at high temperatures, the coupling agent is prone to failure and cannot meet the needs of stress monitoring. Therefore, in response to actual needs, an inorganic adhesive that can couple at high temperatures is developed to couple ultrasound, which has important scientific research value and application value. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a high-temperature coupled inorganic composite adhesive material and a preparation method and application thereof. The present invention makes full use of the performance advantages of high-entropy metals, ceramic materials and inorganic materials to prepare a high-temperature coupled inorganic composite adhesive material and apply it to coupled ultrasound, providing a new idea for the research and development of new ultrasonic coupling materials.

[0008] In a first aspect, the present invention provides a high-temperature coupled inorganic composite adhesive material, which is realized by adopting the following technical solution.

[0009] A high-temperature coupled inorganic composite adhesive material, comprising an inorganic adhesive matrix, a high-entropy metal toughening material, and a ceramic wear-resistant and impact-resistant material; the inorganic adhesive matrix is ​​borate, the high-entropy metal toughening material is AgCuNiCr, and the ceramic wear-resistant and impact-resistant material is B 4 C.

[0010] Furthermore, the inorganic colloid matrix is ​​a mixture of sodium borate and aluminum borate, wherein NaBO 3 :40-60at.%AlBO 3 :40-60at.%; the crystal structure is body-centered cubic system.

[0011] Furthermore, the crystal structure of the high entropy metal toughening material AgCuNiCr is a face-centered square metal, and the contents of the four elements in AgCuNiCr are Ag: 10-20at.%, Cu: 25-40at.%, Ni: 25-35at.%, and Cr: 20-25at.%.

[0012] Furthermore, ceramic wear-resistant and impact-resistant material B 4The particle diameter of C ceramic powder is 5-15 microns.

[0013] Furthermore, the content of the inorganic adhesive matrix in the inorganic composite adhesive material is 50-70wt.%, the content of the high entropy metal toughening material is 10-20wt.%, and the content of the ceramic wear-resistant and impact-resistant material is 10-30wt.%.

[0014] In a second aspect, the present invention provides a method for preparing a high-temperature coupled inorganic composite adhesive material, which is achieved by adopting the following technical solution.

[0015] A method for preparing the above-mentioned high temperature coupling inorganic composite adhesive material comprises the following steps:

[0016] S1. The Ag, Cu, Ni, and Cr alloy materials are ball-milled to prepare a high entropy alloy, the ball-milling time is 8-10 hours, and the powder diameter is 1-10 microns;

[0017] S2. Mechanical stirring method was used to 3 The solution is stirred for 30-50 minutes;

[0018] S3. AgCuNiCr high entropy alloy powder with NaBO and AlBO 3 The mixed solution is mixed by mechanical stirring for 20-40 minutes;

[0019] S4. B 4 C powder is added to the NaBO, AlBO mixed with AgCuNiCr high entropy alloy powder. 3 In the solution, a mechanical stirring method is adopted with a stirring time of 30-60 minutes to obtain a high-temperature coupled inorganic composite adhesive material.

[0020] In a third aspect, the present invention provides a use of a high-temperature coupled inorganic composite adhesive material, which is achieved by adopting the following technical solution.

[0021] An application of the above-mentioned high-temperature coupled inorganic composite adhesive material in oil production bolt stress monitoring.

[0022] Furthermore, the high temperature coupling inorganic composite adhesive material and the ultrasonic probe are bonded and cured at 100-500° C. to form a high temperature resistant ultrasonic monitoring probe for monitoring bolt stress.

[0023] This application has the following beneficial effects.

[0024] (1) The present invention uses high entropy powder, ceramic powder and high temperature resistant inorganic glue to synergistically prepare bonding materials, changing the current situation that there is no coupling agent that can withstand long-term high temperature, and provides a new idea for the research and development of high temperature coupling agents;

[0025] (2) The present invention applies high entropy and high toughness powder to inorganic glue, which can change the problem of high brittleness of inorganic glue after high temperature curing, so that the inorganic glue has a certain toughness and has better tolerance when it is subjected to high and low temperature cycles;

[0026] (3) Present invention B 4 The addition of C powder further strengthens the high temperature adhesive, reduces its curing stress and avoids cracking.

[0027] (4) The present invention applies high-temperature coupled inorganic composite adhesive materials to stress monitoring of oil production bolts, which can monitor the health status of the bolts in real time, and is of great value in ensuring the safety of oil production bolts. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic structural diagram of the high temperature coupled inorganic composite adhesive material of the present invention.

[0029] Among them, 1. Inorganic glue matrix; 2. B 4 C ceramic powder; 3. AgCuNiCr high entropy metal powder. DETAILED DESCRIPTION

[0030] The present patent application is further described below in conjunction with embodiments.

[0031] Example 1

[0032] A method for preparing a high temperature coupled inorganic composite adhesive material comprises the following steps:

[0033] (1) The composition of the composite adhesive is controlled to be 50wt.% of the inorganic adhesive matrix, 20wt.% of the metal toughening material, and 30wt.% of the ceramic wear-resistant and impact-resistant material;

[0034] (2) Ag, Cu, Ni, and Cr alloy materials are ball-milled to prepare a high entropy alloy, and the ball-milling time is 8 hours; the contents of the four elements in AgCuNiCr are Ag: 10at.%; Cu: 30at.%; Ni: 35at.%; Cr: 25at.%; and the powder diameter is 1 micron;

[0035] (3) The inorganic colloid matrix is ​​borate MBO 3 , whose composition is NaBO 3 :40at.%;AlBO 3 :60at.%; Its crystal structure is body-centered cubic system; NaBO and AlBO are stirred by mechanical stirring method 3 The solution was stirred for 30 min;

[0036] (4) AgCuNiCr high entropy alloy powder and MBO 3The solutions were mixed by mechanical stirring for 20 min.

[0037] (5) B 4 C powder added to the mixed AgCuNiCr high entropy alloy powder MBO 3 In the solution, mechanical stirring method was used, and the stirring time was 30min;

[0038] (6) The material is bonded to the ultrasonic probe and cured at a high temperature of 100°C to form a high temperature resistant ultrasonic monitoring probe for monitoring. The high temperature coupling inorganic composite adhesive material directly connects the high temperature resistant ultrasonic probe and the oil production bolt. The function of the high temperature ultrasonic probe is to generate ultrasonic waves during detection. The ultrasonic waves penetrate to the bottom of the bolt through the high temperature resistant inorganic adhesive layer and then return to the probe. The high temperature coupling inorganic composite adhesive material of the present invention can well couple the ultrasonic probe and the surface of the oil production equipment bolt, thereby meeting the monitoring requirements of coupling ultrasonic waves into the bolt under high temperature conditions.

[0039] Example 2

[0040] A method for preparing a high temperature coupled inorganic composite adhesive material comprises the following steps:

[0041] (1) The composition of the composite adhesive is controlled to be 70wt.% of the inorganic adhesive matrix, 10wt.% of the metal toughening material, and 20wt.% of the ceramic wear-resistant and impact-resistant material;

[0042] (2) Ag, Cu, Ni, and Cr alloy materials were ball-milled to prepare a high entropy alloy, and the ball-milling time was 10 hours; the contents of the four elements in AgCuNiCr were Ag: 20 at. %; Cu: 30 at. %; Ni: 25 at. %; Cr: 25 at. %; and the powder diameter was 10 μm;

[0043] (3) The inorganic colloid matrix is ​​borate MBO 3 , whose composition is NaBO 3 :60at.%;AlBO 3 :40at.%; Its crystal structure is body-centered cubic system; NaBO and AlBO are stirred by mechanical stirring method 3 The solution was stirred for 50 min;

[0044] (4) AgCuNiCr high entropy alloy powder and MBO 3 The solutions were mixed by mechanical stirring for 40 min.

[0045] (5) B 4 C powder added to the mixed AgCuNiCr high entropy alloy powder MBO 3In the solution, mechanical stirring method was used, and the stirring time was 60min;

[0046] (6) The material is bonded to the ultrasonic probe and cured at a high temperature of 500°C to form a high temperature resistant ultrasonic monitoring probe for monitoring. The high temperature coupling inorganic composite adhesive material directly connects the high temperature resistant ultrasonic probe and the oil production bolt. The function of the high temperature ultrasonic probe is to generate ultrasonic waves during detection. The ultrasonic waves penetrate through the high temperature resistant inorganic adhesive layer to the bottom of the bolt and then return to the probe. The high temperature coupling inorganic composite adhesive material of the present invention can well couple the ultrasonic probe and the surface of the oil production equipment bolt, thereby meeting the monitoring requirements of coupling ultrasonic waves into the bolt under high temperature conditions.

[0047] Example 3

[0048] A method for preparing a high temperature coupled inorganic composite adhesive material comprises the following steps:

[0049] (1) The composition of the composite adhesive is controlled to be 60wt.% of the inorganic adhesive matrix, 20wt.% of the metal toughening material, and 20wt.% of the ceramic wear-resistant and impact-resistant material;

[0050] (2) Ag, Cu, Ni, and Cr alloy materials were ball-milled to prepare a high entropy alloy, and the ball-milling time was 10 hours; the contents of the four elements in AgCuNiCr were Ag: 20 at.%; Cu: 25 at.%; Ni: 35 at.%; Cr: 20 at.%; and the powder diameter was 8 μm;

[0051] (3) The inorganic colloid matrix is ​​borate MBO 3 , whose composition is NaBO 3 :40at.%;AlBO 3 :60at.%; Its crystal structure is body-centered cubic system; NaBO and AlBO are stirred by mechanical stirring method 3 The solution was stirred for 40 min;

[0052] (4) AgCuNiCr high entropy alloy powder and MBO 3 The solution was mixed by mechanical stirring for 30 min;

[0053] (5) B 4 C powder added to the mixed AgCuNiCr high entropy alloy powder MBO 3 In the solution, mechanical stirring method was used, and the stirring time was 50min;

[0054] (6) The material is bonded to the ultrasonic probe and cured at a high temperature of 200°C to form a high temperature resistant ultrasonic monitoring probe for monitoring. The high temperature coupling inorganic composite adhesive material directly connects the high temperature resistant ultrasonic probe and the oil production bolt. The function of the high temperature ultrasonic probe is to generate ultrasonic waves during detection. The ultrasonic waves penetrate to the bottom of the bolt through the high temperature resistant inorganic adhesive layer and then return to the probe. The high temperature coupling inorganic composite adhesive material of the present invention can well couple the ultrasonic probe and the surface of the oil production equipment bolt, thereby meeting the monitoring requirements of coupling ultrasonic waves into the bolts under high temperature conditions.

[0055] Example 4

[0056] A method for preparing a high temperature coupled inorganic composite adhesive material comprises the following steps:

[0057] (1) The composition of the composite adhesive is controlled to be 55wt.% of the inorganic adhesive matrix, 15wt.% of the metal toughening material, and 30wt.% of the ceramic wear-resistant and impact-resistant material;

[0058] (2) Ag, Cu, Ni, and Cr alloy materials were ball-milled to prepare a high entropy alloy, and the ball-milling time was 9 hours; the contents of the four elements in AgCuNiCr were Ag: 20 at. %; Cu: 25 at. %; Ni: 30 at. %; Cr: 25 at. %; and the powder diameter was 5 μm;

[0059] (3) The inorganic colloid matrix is ​​borate MBO 3 , whose composition is NaBO 3 :50at.%;AlBO 3 :50at.%; Its crystal structure is body-centered cubic system; NaBO and AlBO are stirred by mechanical stirring method 3 The solution was stirred for 40 min;

[0060] (4) AgCuNiCr high entropy alloy powder and MBO 3 The solution was mixed by mechanical stirring for 30 min;

[0061] (5) B 4 C powder added to the mixed AgCuNiCr high entropy alloy powder MBO 3 In the solution, mechanical stirring method was used, and the stirring time was 40min;

[0062] (6) The material is bonded to the ultrasonic probe and cured at a high temperature of 400°C to form a high temperature resistant ultrasonic monitoring probe for monitoring. The high temperature coupling inorganic composite adhesive material directly connects the high temperature resistant ultrasonic probe and the oil production bolt. The function of the high temperature ultrasonic probe is to generate ultrasonic waves during detection. The ultrasonic waves penetrate to the bottom of the bolt through the high temperature resistant inorganic adhesive layer and then return to the probe. The high temperature coupling inorganic composite adhesive material of the present invention can well couple the ultrasonic probe and the surface of the oil production equipment bolt, thereby meeting the monitoring requirements of coupling ultrasonic waves into the bolt under high temperature conditions.

[0063] Example 5

[0064] A method for preparing a high temperature coupled inorganic composite adhesive material comprises the following steps:

[0065] (1) The composition of the composite adhesive is controlled to be 66wt.% of the inorganic adhesive matrix, 20wt.% of the metal toughening material, and 14wt.% of the ceramic wear-resistant and impact-resistant material;

[0066] (2) Ag, Cu, Ni, and Cr alloy materials were ball-milled to prepare a high entropy alloy, and the ball-milling time was 9 hours; the contents of the four elements in AgCuNiCr were Ag: 20 at.%; Cu: 30 at.%; Ni: 30 at.%; Cr: 20 at.%; and the powder diameter was 7 μm;

[0067] (3) The inorganic colloid matrix is ​​borate MBO 3 , whose composition is NaBO 3 :50at.%;AlBO 3 :50at.%; Its crystal structure is body-centered cubic system; NaBO and AlBO are stirred by mechanical stirring method 3 The solution was stirred for 40 min;

[0068] (4) AgCuNiCr high entropy alloy powder and MBO 3 The solution is mixed by mechanical stirring for 20-40 minutes;

[0069] (5) B 4 C powder added to the mixed AgCuNiCr high entropy alloy powder MBO 3 In the solution, mechanical stirring method was used, and the stirring time was 50min;

[0070] (6) The material is bonded to the ultrasonic probe and cured at a high temperature of 400°C to form a high temperature resistant ultrasonic monitoring probe for monitoring. The high temperature coupling inorganic composite adhesive material directly connects the high temperature resistant ultrasonic probe and the oil production bolt. The function of the high temperature ultrasonic probe is to generate ultrasonic waves during detection. The ultrasonic waves penetrate to the bottom of the bolt through the high temperature resistant inorganic adhesive layer and then return to the probe. The high temperature coupling inorganic composite adhesive material of the present invention can well couple the ultrasonic probe and the surface of the oil production equipment bolt, thereby meeting the monitoring requirements of coupling ultrasonic waves into the bolt under high temperature conditions.

[0071] Performance Testing

[0072] The tensile strength of the inorganic composite adhesive materials prepared in Examples 1-5 of the present application was tested (refer to GB / T6329-1996). The test results are shown in Table 1.

[0073] Table 1 Composite adhesive properties tensile strength test (unit: MPa)

[0074]

[0075] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature coupling inorganic composite adhesive material, characterized in that: It includes an inorganic glue matrix, a high entropy metal toughening material, and a ceramic wear-resistant and impact-resistant material; the inorganic glue matrix is ​​borate, the high entropy metal toughening material is AgCuNiCr, and the ceramic wear-resistant and impact-resistant material is B4C.

2. The high temperature coupling inorganic composite adhesive material according to claim 1, characterized in that: The inorganic colloid matrix is ​​a mixture of sodium borate and aluminum borate, wherein NaBO3: 40-60at.%, AlBO3: 40-60at.%, and the crystal structure is a body-centered cubic system.

3. The high temperature coupling inorganic composite adhesive material according to claim 1, characterized in that: The crystal structure of the high entropy metal toughening material AgCuNiCr is a face-centered square metal, and the contents of the four elements in AgCuNiCr are Ag: 10-20at.%, Cu: 25-40at.%, Ni: 25-35at.%, Cr: 20-25at.%.

4. The high temperature coupling inorganic composite adhesive material according to claim 1, characterized in that: The particle diameter of the ceramic wear-resistant and impact-resistant material B4C ceramic powder is 5-15 microns.

5. The high temperature coupling inorganic composite adhesive material according to claim 1, characterized in that: The content of inorganic adhesive matrix in the inorganic composite adhesive material is 50-70wt.%, the content of high entropy metal toughening material is 10-20wt.%, and the content of ceramic wear-resistant and impact-resistant material is 10-30wt.%.

6. A method for preparing the high temperature coupling inorganic composite adhesive material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The Ag, Cu, Ni, and Cr alloy materials were ball-milled to prepare a high entropy alloy, the ball-milling time was 8-10 hours, and the powder diameter was 1-10 microns; S2. The NaBO and AlBO3 solutions were stirred by mechanical stirring for 30-50 min; S3. The AgCuNiCr high entropy alloy powder was mixed with a mixed solution of NaBO and AlBO3 by mechanical stirring for 20-40min; S4. Add B4C powder to NaBO and AlBO3 solution of mixed AgCuNiCr high entropy alloy powder, and use mechanical stirring method for 30-60 minutes to obtain high temperature coupled inorganic composite adhesive material.

7. Use of the high temperature coupled inorganic composite adhesive material according to any one of claims 1 to 5 in stress monitoring of oil production bolts.

8. The application according to claim 7, characterized in that: The high temperature coupling inorganic composite adhesive material and the ultrasonic probe are bonded and cured at a high temperature of 100-500°C to form a high temperature resistant ultrasonic monitoring probe for monitoring bolt stress.